2008
DOI: 10.1038/sj.bjc.6604782
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous blockade of AP-1 and phosphatidylinositol 3-kinase pathway in non-small cell lung cancer cells

Abstract: c-Jun is a major constituent of AP-1 transcription factor that transduces multiple mitogen growth signals, and it is frequently overexpressed in non-small cell lung cancers (NSCLCs). Earlier, we showed that blocking AP-1 by the overexpression of a c-Jun dominant-negative mutant, TAM67, inhibited NSCLC cell growth. The phosphatidylinositol 3-kinase (PI3K)/Akt signal transduction pathway is important in transformation, proliferation, survival and metastasis of NSCLC cells. In this study, we used NCI-H1299 Tet-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…We have previously shown that blocking AP-1 transcription factor by TAM67 inhibited the growth of NSCLC cells [3,4]. We confirmed that the induction of TAM67 decreased expression of MCM4 and inhibition of MCM4 expression by siRNA reduced cell proliferation in H1299 cell, thus suggesting that TAM67 inhibits cell proliferation partially due to reduced expression of MCM4 in H1299 cells.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We have previously shown that blocking AP-1 transcription factor by TAM67 inhibited the growth of NSCLC cells [3,4]. We confirmed that the induction of TAM67 decreased expression of MCM4 and inhibition of MCM4 expression by siRNA reduced cell proliferation in H1299 cell, thus suggesting that TAM67 inhibits cell proliferation partially due to reduced expression of MCM4 in H1299 cells.…”
Section: Discussionsupporting
confidence: 89%
“…1A, [3,4]). To identify downstream effectors relevant to the growth inhibition, we performed microarray analysis.…”
Section: Induction Of a Cjun Dominant-negative Mutant Tam67 Decreasementioning
confidence: 97%
See 1 more Smart Citation
“…JUN is a proto-oncogene, expression of c-Jun promotes cellular survival by negatively regulating the expression of the tumor-suppressor PTEN (35). c-Jun is a major constituent of AP-1 transcription factor that transduces multiple mitogen growth signals (36). Expression of AP-1 proteins has been associated with a more aggressive clinical outcome in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our experimental research further revealed the molecular mechanism for the synergistic increase of transforming activity by coexposure to Cr and As. Since the PI3K/AKT signaling pathway has been reported to be involved in the transformation of various cancers including lung carcinoma (Kikuchi et al, 2008;Patek et al, 2008;Molina-Arcas et al, 2013;Thang et al, 2015), synergistic activation of the PI3K/AKT signaling pathway by co-exposure to Cr and As may be involved in the increased transforming activity of BEAS-2B human lung epithelial cells.…”
Section: Biological Effects Of Co-exposure To Cr Cu and As On Human mentioning
confidence: 99%